2022
DOI: 10.1039/d2nj00911k
|View full text |Cite
|
Sign up to set email alerts
|

Structure, bonding and adaptive aromaticity in rhenium-oxo complexes: a DFT study

Abstract: In general, species could be aromatic in the ground or excited state only according to Hückel’s and Baird’s rules. Thus, adaptive aromatics are particularly rare as they can be aromatic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…More precisely, it is adaptive π-aromaticity in this case because both the aromaticities in the two states stem from the π-electron delocalization. Afterwards, they continually discovered adaptive π-aromaticity in more organometallics such as metallapentalene/metallapyridinium, 11–15 metallazapentalene 16 and metallasilapentalyne complexes. 17 These contributions greatly enrich the metallaaromatic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…More precisely, it is adaptive π-aromaticity in this case because both the aromaticities in the two states stem from the π-electron delocalization. Afterwards, they continually discovered adaptive π-aromaticity in more organometallics such as metallapentalene/metallapyridinium, 11–15 metallazapentalene 16 and metallasilapentalyne complexes. 17 These contributions greatly enrich the metallaaromatic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, our previous studies on organometallic species suggest that the trend of NICS values is consistent with other aromatic indices. 31,34,65,66 So the NICS(1) zz values are used to evaluate aromaticity in this work. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The loss of triplet state aromaticity of the Ir.X species encouraged us to explore the distribution of unpaired electrons in their lowest triplet state. Moreover, recent studies have demonstrated that spin density 28,31,34,66 plays an important role in adaptive aromaticity. The Mulliken spin populations on the metal center atoms and the remaining fragment (C 4 N) of the six-membered ring in the M.X species are provided in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations